2018
DOI: 10.1186/s12894-018-0319-6
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion as an independent predictor of biochemical recurrence in prostate cancer following radical prostatectomy or radiotherapy: a systematic review and meta-analysis

Abstract: BackgroundAlthough numerous studies have shown that perineural invasion (PNI) is linked to prostate cancer (PCa) risk, the results have been inconsistent. This study aimed to explore the association between PNI and biochemical recurrence (BCR) in patients with PCa following radical prostatectomy (RP) or radiotherapy (RT).MethodsAccording to the PRISMA statement, we searched the PubMed, EMBASE, Chinese National Knowledge Infrastructure (CNKI) and Wan Fang databases from inception to May 2017. Hazard ratios (HRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
2
38
1
Order By: Relevance
“…24 The importance of a perineurial invasion detected in a prostate biopsy specimen is controversial. 25 In the present study, we did not find a relation between perineural invasion and PSM.…”
Section: Discussioncontrasting
confidence: 72%
“…24 The importance of a perineurial invasion detected in a prostate biopsy specimen is controversial. 25 In the present study, we did not find a relation between perineural invasion and PSM.…”
Section: Discussioncontrasting
confidence: 72%
“…It has been reported that PNI was significantly associated with recurrence and poor survival outcome in pancreatic cancer, prostate cancer and colorectal cancer 11–14. Furthermore, there have been several studies evaluating the prognostic significance of PNI for GC patients, but the results were conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, its incidence varies among different studies, with a proportion ranging from 23% to 90% in the radical prostatectomy (RP) specimen and 7% to 43% in the biopsy specimen (Harnden et al ., ; Merrilees et al ., ; Masieri et al ., ; Tollefson et al ., ). Although the exact clinical value of PNI remains controversial (Zareba et al ., ; Zhang et al ., ), the presence of PNI is still considered as one of the important mechanisms of PCa cells spreading beyond the prostate (Villers et al ., ). Remarkably, apart from the classic routes of metastatic spread of tumor cells, for example, lymphatic and hematogenous, peripheral nerve is also recognized as a crucial route of PCa spreading.…”
Section: Introductionmentioning
confidence: 99%